Acceptance of Increasing the Productivity of Spring Barley - Ryabtseva , Natalya; Avdeenko, Aleksey; Avdeenko, Svetlana; Fetyukhin, Igor (KnE Life Sciences, 2021)
The aim of this research was to develop a model of productive agrocenoses of spring barley through the application of the growth regulators Biroduks, Vitazim, Emistim and Ribav-Extra. Spraying the plants with the growth regulators led to better growth and the development of leaf blades: the leaf area on one plant increased 1.2-1.74 times. The activation of photosynthetic activity using biological products was established. The most developed assimilation apparatus of the plant was developed under the drug Emistim: the leaf area was 69.224 m2 / ha. The weight of 1000 grains was at its maximum under the influence of Emistim (45.9 g). Less heavy grain was formed by crops under the influence of the Biroduks preparation (45.7 g). In version three, the weight of 1000 grains exceeded the control by 1.9 g. In version five, the increase was 1.4 g. The relationship between the mass of 1000 grains, productive bushiness and yield was a weak straight line (r = 0.19 and r = 0.16, respectively). The increase in yield depended to a greater extent on the number of preserved plants for harvesting (r = 0.98) than on the mass of the grain, the bushiness or the number of grains in the ear. The minimum biological yield was obtained in the control variant and the maximum was with the drug Emistim. Reliability at a 95% significance level was noted on all options. The positive impact on overcoming stressful effects during the growing season of spring barley was most effective when using the drug Emistim. Keywords: spring barley, plant growth regulator, efficiency